How healthcare professionals transition from being self-employed to being employees: The case of French medical biologists - Lucas Dufour; Meena Andiappan; Arnaud Banoun (Elsevier, 2023)
The past decades have seen a significant rise in the number of large-scale commercial enterprises entering the healthcare sector, making it difficult for smaller companies and entrepreneurs to remain competitive. This change has meant that an increasing number of healthcare professionals have transitioned from being self-employed entrepreneurs to being company employees. How do healthcare professionals manage this (often reluctant) transition and its resulting tensions? Based on qualitative data (including 40 interviews, 18 ​h of observation, and 314 archival records) with French medical biologists, we employ the economies of worth framework developed by Boltanski and Thévenot (1991, 2006) to understand the strains healthcare professionals experience related to a coerced change of perspective and how their organization, in turn, uses various strategies to address these tensions. We find that medical biologists experience tensions related to their domestic perspective due to the change of their employment status (from self-employed to company employee) and related to their industrial perspective due to the repositioning of their job (from scientific expert to site manager). To address these concerns, their organization first applied a civic perspective, with mixed results. Searching for a more successful approach, the organization pivoted to a domestic perspective, which was largely counterproductive. Tensions were finally stabilized when the organization developed a structure based on both civic and network principles. Our paper contributes to the literature through demonstrating that tensions need to be resolved at an organizational level first without rushing through a compromise in order to achieve clarification at an individual level.